Analysing the Indonesian Government’s Measures in Dealing with the Humanitarian Crisis of the Asylum-Seekers of Rohingya - Muhamad Arby Hariawan (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Presently, Indonesia is facing multitudinous arrival waves of Rohingya immigrants due to the existing conflict between the military junta of Myanmar and Rohingya communities in Rakhine State. In spite of the authorities of Indonesia have not signed the Convention of 1951 and the Protocol of 1967 about the asylum-seekers, on the other hand, Indonesia is still opening its border for the earlier displaced people due to several humanitarian-related regulations: the second point of Pancasila, the article 28 G verse 2, and the Act Number 39 Year 1999. This paper evaluates measures of the Indonesian governments in handling the asylum-seekers of Rohingya by using the Theory of the Humanitarian Assistances for the Refugees which contains several aspects namely: Coordination, (2) Clear Policies, (3) Humanitarian Actors, (4) Humanitarian Spaces, (5) Crisis Contingency Plans, and (6) Impacts to the Social. Required data is gained by several techniques such as doing interviews, analyzing literature study, and making observations. The research reveals that in general, the governments of Indonesia have implemented required schemes such as (1) doing coordination with numerous stakeholders, (2) having clear regulations as guidelines, (3) mapping humanitarian parties, (4) allocating temporary settlements, and (5) preventing the future risks. However, for preventing social conflict with local people, the governments were not optimal in doing two agendas: making assimilation and ceasing the circulation of disinformation about Rohingya people on the internet.